The Manila teachers' movement: History, challenges, prospects - Moratilla, Noel Christian A. (Animo Repository, 2011)
This paper traces the progress of the teachers’ movement of the City of Manila, said to be most militant in the region, during the period 1946-2006. In particular, the discussion foregrounds the evolution of the teachers’ movement within specific but always shifting social and historical contexts, including the role played by the movement in vital issues ranging from salary increases to broader concerns, such as the anti-dictatorship struggle of the 1970’s and the economic and political crises of the succeeding decades. Likewise discussed is the present status of the movement vis-à-vis the sector’s most pressing agenda and “intramural” challenges such as the ideological differences among teachers’ organizations.